SH sodium alginate gel and its application in establishing animal model of bone echinococcosis

By designing the optimized SH sodium alginate gel, the problems of poor mechanical properties of existing gels and difficult to judge the efficacy of drug treatment are solved, the controllability of the gel and the drug capture effect are achieved, the construction cycle of animal models is shortened, and the construction of animals is improved. Efficiency of treatment effect assessment.

CN119097638BActive Publication Date: 2025-02-25SHANDONG UNIV QILU HOSPITAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411259982.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-02-25
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing natural polymer polysaccharide gel has poor mechanical properties, is too high to swell and is too fast to degrade, resulting in limited application and difficult to achieve precise regulation of gels. Especially in the treatment of hydatosis, it is difficult for drugs to When the lesions accumulate, the treatment effect is difficult to judge in a short period of time.

Method used

A functionally regulated SH sodium alginate gel was designed. By optimizing the crosslinking degree of inner core and shell structure, the controllability of the gel was significantly improved, drug capture and concentration detection were realized, and animal models were shortened. Build cycle.

Benefits of technology

SH sodium alginate gel has good adsorption performance and stability, can effectively capture and release drugs, shorten the animal model construction cycle, and improve the evaluation efficiency of treatment effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119097638B_ABST
    Figure CN119097638B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of polysaccharides or hydrogels, and relates to a SH sodium alginate gel and its application in the establishment of an animal model of bone echinococcosis. The SH sodium alginate gel comprises an inner core and an outer shell, wherein the inner core is cross-linked sodium hyaluronate and sodium hyaluronate, the outer shell is a cross-linked sodium alginate gel, the inner core has an increasing degree of cross-linking of sodium hyaluronate from the inside to the outside, and the components of the sodium alginate gel include glycerol. By designing the structure of the inner core and the outer shell, and optimizing the cross-linking degree of the inner and outer matrices, the controllability of the SH sodium alginate gel is significantly improved, and good applications are achieved in aspects such as in vitro and in vivo drug detection and substance concentration absorption model construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polysaccharides or hydrogels, and relates to SH sodium alginate gel and application thereof in establishing an animal model of bone echinococcosis. Background Art

[0002] Functionalized gels prepared with natural high molecular weight polysaccharides (such as starch, xanthan gum, dextran, chitosan, sodium alginate, guar gum, carrageenan, etc.) have multiple functions such as filling support, capture and adsorption. They have a biological tissue-like structure and good biocompatibility. They have multiple uses in in vivo detection and substance transportation.

[0003] Especially in terms of substance capture or sustained release, based on the gel swelling characteristics, functionalized gels can achieve directional and quantitative transport effects to a certain extent. However, the gels prepared from natural high molecular weight polysaccharides have poor mechanical properties, excessive swelling, and rapid degradation rates, which limit their applications. Considering the swelling rate, substance release rate, and gel degradation rate, how to achieve precise control of the gel is also an urgent problem to be solved in this field.

[0004] At present, the main treatment for bone echinococcosis is surgery, but the recurrence rate of surgery is high. Some bone parts are not suitable for surgery. The risk of bone damage caused by surgery is high or it is difficult to perform surgical treatment. Therefore, drugs are currently selected for treatment in such cases, such as albendazole, etc., but drug treatment also has its limitations. It is difficult for drugs to accumulate in lesions, and it is difficult to explore the effective concentration of drugs in different parts (especially joint bones). It is difficult to judge the therapeutic effect in a short time. Especially when constructing an animal model of bone echinococcosis, the protoscolecus of Echinococcus granulosus is usually prepared by direct inoculation. The culture process takes 12 to 16 months, the cycle is long, the infection rate is low, and the mortality rate is high. Based on this, the present invention constructs a hydatid cyst model with SH sodium alginate gel, and the therapeutic effect is inferred by capturing the drug concentration with SH sodium alginate gel. This application greatly shortens the animal model construction cycle, or can be used for the analysis of the osteogenesis effect of other bone defect diseases. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a functional and controllable SH sodium alginate gel and a preparation method thereof, and application in the establishment of an animal model of bone echinococcosis. By designing the inner core and outer shell structure and optimizing the cross-linking degree of the inner and outer matrices, the controllability of the SH sodium alginate gel is significantly improved, and good applications are achieved in in vitro and in vivo drug detection, substance concentration absorption model construction, etc.

[0006] The specific technical solutions of the present invention are as follows:

[0007] A functional and adjustable SH sodium alginate gel, the SH sodium alginate gel comprising an inner core and an outer shell, the inner core is cross-linked sodium hyaluronate and sodium hyaluronate, the outer shell is a cross-linked sodium alginate gel, the cross-linking degree of sodium hyaluronate in the inner core increases from the inside to the outside, and the components of the sodium alginate gel include glycerol.

[0008] Furthermore, the SH sodium alginate gel is a sphere, and the shell thickness is 0.1-3 mm.

[0009] The present invention also provides a method for preparing a functional and controllable SH sodium alginate gel, the preparation method comprising the following steps:

[0010] (1) dissolving sodium alginate in a 0.1 M acetic acid aqueous solution to prepare a 5-10 wt% polysaccharide solution, adding 2% (volume) glycerol, adding a cross-linking agent, mixing and cross-linking, and drying at 60° C. for 5 h to obtain a cross-linked sodium alginate gel;

[0011] (2) Sodium hyaluronate with a molecular weight of 0.5-1 million Da was injected into the sodium alginate gel to obtain a mixed gel A. The mixed gel A was immersed in a 0.4% (volume) BDDE solution for 15-30 min, taken out, and dried at 60°C for 3 h to obtain SH sodium alginate gel.

[0012] Furthermore, in some applications, when the mass proportion of sodium hyaluronate as the inner core is less than 5%, the mixed gel A does not need to be immersed in a 0.4% (volume) BDDE solution.

[0013] Furthermore, in (1), the crosslinking agent is Ca 2+ solution or borax solution; further, the Ca 2+ The concentration of the solution is 0.12 mol / L, and the borax solution is a borax aqueous solution with a concentration of 4 wt %.

[0014] Furthermore, in (2), the mass ratio of sodium hyaluronate to sodium alginate gel is 1:3-6.

[0015] Furthermore, in (2), sodium hyaluronate with a molecular weight of 0.5 to 1 million Da is injected into the cross-linked sodium alginate gel using a microneedle, and the resulting mixed gel A is suitable for preparing SH sodium alginate gel with an average particle size of more than 2 mm.

[0016] Furthermore, in (2), sodium hyaluronate with a molecular weight of 0.5 to 1 million Da is dispersed in a 1% (volume) NaOH aqueous solution, emulsified at 4000 rpm in a stirrer for 20 min, and polysaccharide is added to encapsulate the sodium hyaluronate to obtain a mixed gel A.

[0017] Furthermore, the mixed gel A was immersed in a 0.4% (volume) BDDE solution for 15-30 min, taken out, and dried at 60° C. for 3 h to obtain SH sodium alginate gel (average particle size 0.1-0.8 mm).

[0018] The present invention also provides an application of SH sodium alginate gel in preparing a material absorption model, by controlling the shell thickness and the inner core crosslinking degree of the SH sodium alginate gel to regulate the capture and release capabilities of different substances, and the application includes the concentration detection of drugs and metal ions.

[0019] Furthermore, the present invention provides an application of SH sodium alginate gel in establishing an animal model of bone hydatid disease, characterized in that the application includes placing the SH sodium alginate gel at a bone hydatid disease modeling site to obtain drug concentration data at the bone hydatid disease modeling site, specifically, implanting the SH sodium alginate gel into the bone marrow cavity or bone defect modeling site of the model animal, administering the drug to the animal, and when the theoretical blood drug concentration peak value or a preset culture period (<30 days) is reached, taking out the SH sodium alginate gel, drying, crushing and soaking it, and detecting the drug concentration absorbed by the SH sodium alginate gel, thereby calculating the drug efficacy at the bone hydatid disease site of the animal model.

[0020] The beneficial effects of the present invention are:

[0021] 1. The SH sodium alginate gel of the present invention has good adsorption properties, and can achieve substance capture or concentration detection by regulating the cross-linking degree of the outer shell sodium alginate or changing the pH of the external environment. The present invention constructs a progressive cross-linked sodium hyaluronate by controlling the cross-linking time. After sodium hyaluronate wraps the cross-linked sodium alginate, in a liquid environment, the outer layer of sodium alginate swells first, and the material exchange is enhanced. As the swelling time increases, under the action of osmotic pressure, the drug can accumulate inside the sodium hyaluronate, especially in the inner core with a low degree of cross-linking, to achieve the capture of the substance.

[0022] 2. By designing the shell and core structure of SH sodium alginate gel and using sodium alginate or guar gum to construct a shell with a low maximum swelling degree, the rapid swelling of sodium hyaluronate in a low osmotic liquid environment is effectively limited, and the sol transition caused by the long-term swelling of cross-linked sodium hyaluronate is directly avoided, which significantly improves the overall stability of SH sodium alginate gel. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0024] Figure 1 This is the drug absorption rate curve of SH sodium alginate gel;

[0025] Figure 2 This is the SEM morphology of the outer shell of the longitudinal section of SH sodium alginate gel;

[0026] Figure 3 This is the SEM morphology of the inner core of the longitudinal section of SH sodium alginate gel. DETAILED DESCRIPTION

[0027] The present invention is described below by specific embodiments. Unless otherwise specified, the technical means used in the present invention are methods known to those skilled in the art. In addition, the embodiments should be understood as illustrative rather than limiting the scope of the present invention, and the essence and scope of the present invention are limited only by the claims. For those skilled in the art, various changes or modifications to the material composition and dosage in these embodiments, without departing from the essence and scope of the present invention, also belong to the protection scope of the present invention.

[0028] Example 1

[0029] A method for preparing a functional and adjustable SH sodium alginate gel, comprising the following steps:

[0030] (1) Sodium alginate was dissolved in 0.1 M acetic acid aqueous solution to prepare a 10 wt% sodium alginate solution, 2% (volume) glycerol was added, and 0.12 mol / L Ca 2+ The aqueous solution was mixed and stirred for 10 min until the gel was completely cross-linked, poured into a spherical mold (2 mm in diameter), and dried at 60 °C for 5 h to obtain a cross-linked sodium alginate gel;

[0031] During the step of pouring the cross-linked sodium alginate gel into a mold and drying it, the inventors found that the surface of the gel was often too dry, resulting in damage to the gel shape and affecting its use. Therefore, adding an appropriate amount of glycerol, a water-retaining agent, solved the problem and reduced the surface roughness. Subsequently, the inventors found that the glycerol concentration also had a significant effect on the drug capture function of the SH sodium alginate gel.

[0032] (2) Sodium hyaluronate with a molecular weight of 1 million Da was injected into the spherical sodium alginate gel to obtain mixed gel A. The mixed gel A was immersed in a 0.4% (volume) BDDE solution for 15 min, taken out, and dried at 60°C for 3 h to obtain SH sodium alginate gel.

[0033] Characterization of crosslinking degree:

[0034] In this embodiment, the cross-linking degree of sodium hyaluronate from the inside to the outside of the inner core is gradually increased by soaking in a cross-linking agent. Since the volume of SH sodium alginate gel is too small to be suitable for cross-linking degree detection, the SH sodium alginate gel is cut along the longitudinal section, soaked in distilled water until the morphological changes caused by cutting are restored, and then placed in a freeze dryer for cold winter drying. Figure 2 As shown in Figure 2, the outer shell of SH alginate gel presents a denser porous structure, which indicates that its cross-linking degree is higher, while the inner core ( Figure 3 ) has a larger average pore size, indicating a lower degree of cross-linking than the outer shell.

[0035] Drug capture function study:

[0036] The adsorption and capture effects of sodium alginate shells prepared by different methods and progressively cross-linked sodium hyaluronate cores on albendazole were investigated.

[0037] Experimental method: SH sodium alginate gel was divided into groups 1, 2, and 3, immersed in SBF simulated body fluid, added with 1 mg / L albendazole, swollen for 2h, 4h, 12h, and 24h, the SH sodium alginate gel was taken out, dried naturally, placed in 2% NaOH solution to swell for 24h, and the drug concentration in the solution was detected.

[0038] Table 1 SH sodium alginate gels prepared with different component concentrations

[0039] Group / Concentration 1 2 3 4 Glycerol concentration 2% (volume) 0 2% (volume) 4% (volume) BDDE solution concentration 0.4% (volume) 0.4% (volume) 1% (volume) 0.4% (volume)

[0040] Table 2 Adsorption effect of each group on albendazole (absorption rate %)

[0041] Group / Time 1 2 3 4 2h 32.5 31.2 31.6 33.1 4h 38.9 336 34.9 39.2 12h 46.7 38.9 32.1 41.6 24h 62.7 51.1 43.1 68.8

[0042] SH sodium alginate gel has a good effect on drug absorption.

[0043] Example 2

[0044] Characterization experiment of SH sodium alginate gel.

[0045] According to the same SH sodium alginate gel preparation method as Example 1, the sodium alginate content was used as a single factor variable to study the fusion degree of sodium hyaluronate and sodium alginate. Four groups of 1wt%, 5wt%, 10wt%, and 15wt% sodium alginate and a control group were constructed based on gel density, viscosity time, and cross-linking degree.

[0046] Table 3 Characterization of SH sodium alginate gel

[0047] Group Sodium alginate concentration <![CDATA[Density / g / cm 2 > Viscosity time / s Crosslinking degree / % 1 1wt% 0.24 50s 23.6% 2 5wt% 1.06 33s 26.1% 3 10wt% 1.12 8s 38.4% 4 15wt% 1.57 6s 40.4%

[0048] It can be seen that the cross-linking time at 10wt% sodium alginate is the shortest, which can quickly construct the three-dimensional network of the gel, which is beneficial to maintaining the shell structure. However, a high concentration of sodium alginate (15wt%) causes the gel density to be too high, which is not conducive to the absorption of drugs.

[0049] The SH sodium alginate gel was freeze-dried and the longitudinal section was characterized by scanning electron microscopy. It can be seen that the degree of fusion between sodium hyaluronate and sodium alginate is high, the gel presents a uniform three-dimensional pore structure, and BMSC cells are cultured in the pore gaps. From a more microscopic perspective, sodium alginate and sodium hyaluronate form a similar connected tube wall structure ( Figure 2 ).

[0050] Characterization of the adhesion performance of SH sodium alginate gel: The prepared groups of SH sodium alginate gel in Table 1 were passed through a nanohydroxyapatite plate, and 10 groups of SH sodium alginate gel balls with a diameter of 2 mm were bonded to the nanohydroxyapatite plane. Tension wire ropes were fixed in the balls. The tensile force required to break the SH sodium alginate gel was tested by tensile test, F=-(3 / 2)πE A R, E A is the adhesion energy.

[0051] Table 4 Characterization of adhesion properties and water content of SH sodium alginate gel

[0052] Group Adhesion Energy Water content 1 <![CDATA[27.1J / m 2 ]]> 53.7% 2 <![CDATA[29.3J / m 2 ]]> 51.4% 3 <![CDATA[32.5J / m 2 ]]> 52.5% 4 <![CDATA[58.4J / m 2 ]]> 68.2%

[0053] It can be seen that glycerol significantly enhanced the adhesion performance, but the high water content is not conducive to maintaining the spherical shape and is easily affected by gravity. The SH sodium alginate gel in the other groups has excellent adhesion performance and can be tightly combined with nano-hydroxyapatite. Implanting it into the bone defect area can avoid the gel sedimentation affected by gravity and maximize its effect.

[0054] Example 3

[0055] In this example, SH sodium alginate gel was used to construct an animal model of echinococcosis.

[0056] Surgery is the main method for bone echinococcosis, but the recurrence rate of surgery is high. Some bone parts are not suitable for surgery. The risk of bone damage caused by surgery is high or it is difficult to perform surgical treatment. Therefore, drugs are currently selected for treatment in such cases, such as albendazole, etc. However, drug treatment also has its limitations. It is difficult for drugs to accumulate in lesions, and it is difficult to explore the effective concentration of drugs in different parts (especially joint bones). It is difficult to judge the therapeutic effect in a short time. Especially when constructing an animal model of bone echinococcosis, the protoscolecus of Echinococcus granulosus is usually prepared by direct inoculation. The culture process lasts for 12 to 16 months, with a long cycle, low infection rate and high mortality rate. Based on this, the embodiment of the present invention constructs a hydatid cyst model with SH sodium alginate gel, and the therapeutic effect is inferred by capturing the drug concentration in SH sodium alginate gel. This application greatly shortens the animal model construction cycle, or can be used for the analysis of the osteogenesis effect of other bone defect diseases.

[0057] The application of a functional and controllable SH sodium alginate gel of the present invention in constructing a hydatid cyst model of bone echinococcosis comprises the following steps:

[0058] (1) Soak 2 g of SH sodium alginate gel (particle size 1.5 mm) prepared in Example 1 in a gentamicin aqueous solution for 60 s;

[0059] (2) The mice were implanted into the femoral medullary cavity of 3-month-old New Zealand white rabbits (2 kg ± 0.3 kg). Albendazole was administered at a fixed time daily at 10 mg / kg (animal body weight). The drug concentration in the SH sodium alginate gel was measured at 1, 2, 4, 8, and 16 days after feeding.

[0060] (3) When the blood drug concentration reaches the peak after the last dose, extract or scrape the SH sodium alginate gel, dry it naturally or bake it, pulverize it, immerse it in 2% NaOH solution to swell for 24 hours, and detect the drug concentration in the solution.

[0061] Specifically, the experimental groups were as follows: 20 New Zealand white rabbits were divided into two groups, one of which was a blank control group (no SH sodium alginate gel was implanted) to verify the drug absorption effect of SH sodium alginate gel.

[0062] Drug absorption rate of SH sodium alginate gel = (drug concentration in SH sodium alginate gel - drug concentration in bone marrow cavity) / drug concentration in bone marrow cavity.

[0063] Table 5 Changes in drug concentration in SH sodium alginate gel in animal models

[0064] Detection time / d SH sodium alginate gel drug absorption rate / % Drug concentration in bone marrow cavity of control group 1 10.59 12.3 μg / mL 2 27.8 23.2 μg / mL 4 34.8 26.8 μg / mL 8 48.9 28.3 μg / mL 16 57.3 28.6 μg / mL

[0065] The above data show that the drug absorption rate of SH sodium alginate gel can be obtained according to the blank control group. SH sodium alginate gel can realize drug capture and concentration detection. Figure 1 It can be seen that in the period of 2 to 8 days, the drug absorption rate of SH sodium alginate gel shows a linear relationship, and the modeling effect can be inferred by combining the drug effect.

[0066] It should be additionally noted that the SH sodium alginate gel in vivo for more than 16 days begins to degrade, and the SH sodium alginate gel of the present invention is not suitable for modeling drug testing for more than 30 days.

Claims

1. Application of SH sodium alginate gel in establishing an animal model of bone echinococcosis, characterized in that: The application includes placing SH sodium alginate gel at the bone hydatid cyst modeling site to obtain drug concentration data at the bone hydatid cyst modeling site; The SH sodium alginate gel comprises an inner core and an outer shell, wherein the inner core is cross-linked sodium hyaluronate and sodium hyaluronate, the outer shell is cross-linked sodium alginate gel, the cross-linking degree of sodium hyaluronate in the inner core increases from the inside to the outside, and the components of the SH sodium alginate gel include glycerol; The preparation method of the SH sodium alginate gel comprises the following steps: (1) dissolving sodium alginate in a 0.1 M acetic acid aqueous solution to prepare a 5-10 wt% sodium alginate solution, adding 2% by volume of glycerol, adding a cross-linking agent, mixing and cross-linking, and drying at 60° C. for 5 h to obtain a cross-linked sodium alginate gel; (2) Sodium hyaluronate with a molecular weight of 0.5-1 million Da is injected into a cross-linked sodium alginate gel or is encapsulated by a cross-linked sodium alginate gel in an emulsion to obtain a mixed gel A, and the mixed gel A is immersed in a 0.4% volume BDDE solution for 15-30 minutes, taken out, and dried at 60°C for 3 hours to obtain a SH sodium alginate gel; The mass ratio of the sodium hyaluronate to the cross-linked sodium alginate gel is 1:3-6.

2. The use according to claim 1, characterized in that The SH sodium alginate gel is a sphere, and the shell thickness is 0.1-3 mm.

3. The use according to claim 1, characterized in that (1), the crosslinking agent is Ca 2+ solution or borax solution.

4. The use according to claim 1, characterized in that (2) Sodium hyaluronate with a molecular weight of 0.5 to 1 million Da is injected into the sodium alginate gel using a syringe.

5. The use according to claim 1, characterized in that (2), sodium hyaluronate with a molecular weight of 0.5-1 million Da is dispersed in a 1% volume NaOH aqueous solution, emulsified at 4000 rpm in a stirrer for 20 min, and polysaccharide is added to encapsulate the sodium hyaluronate to obtain a mixed gel A.

Citation Information

Patent Citations

  • Medical sodium alginate gel microsphere and preparation method and application thereof

    CN103239730A

  • Application of azide-modified hyaluronic acid in drug delivery and / or drug storage

    CN116236588A